Hidden Function of Catalytic Domain in 6-Methylsalicylic Acid Synthase for Product Release - Moriguchi, Tomomi (American Society for Biochemistry and Molecular Biology, 2010)
Functional investigation of the proposed dehydratase domain of ATX, a 6-methylsalicylic acid synthase from Aspergillus terreus, revealed that the domain is not involved in dehydration of the β-hydroxytriketide intermediate tethered on the acyl carrier protein but catalyzes thioester hydrolysis to release the product from the acyl carrier protein. Thus, we renamed this domain the thioester hydrolase (TH) domain. The intermediate bound to the TH domain of mutant H972A formed in the presence of NADPH was released as 6-methylsalicylic acid by both the intact ATX and by THID (a 541-amino acid region containing TH domain and its downstream) protein, in trans. Furthermore, THID showed a catalytic activity to hydrolyze a model substrate, 6-methylsalicylic acid-N-acetylcysteamine. The TH domain is the first example of a product-releasing domain that is located in the middle of a multidomain iterative type I polyketide synthase. Moreover, it is functionally different from serine protease-type thioesterase domains of iterative type I polyketide synthases.